2022
DOI: 10.1007/s10508-021-02212-4
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Sexual and Relationship Adjustment During COVID-19

Abstract: The COVID-19 pandemic and the mitigation measures put in place have resulted in universal disruption in the usual ways of life for individuals. The current study sought to investigate how aspects of sexual health (well-being and functioning) and relationship satisfaction changed or remained stable during the pandemic. During two separate time points (Time 1 including Time 1 and a retrospective baseline, Time 2), participants completed online measures of sexual well-being (sexual pleasure, partnered and solitar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 51 publications
2
7
1
Order By: Relevance
“…However, the results of this study did not confirm a direct association between restriction level and sexual satisfaction among Polish participants. The findings are in line with the other longitudinal study from Canada [18] and cross-sectional research from China [39] and Germany [42], which also did not find any changes in sexual satisfaction during the lockdown as compared to the pre-pandemic period. Nomejko et al [15] argue that sexual dysfunction is not always related to lower sexual satisfaction.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…However, the results of this study did not confirm a direct association between restriction level and sexual satisfaction among Polish participants. The findings are in line with the other longitudinal study from Canada [18] and cross-sectional research from China [39] and Germany [42], which also did not find any changes in sexual satisfaction during the lockdown as compared to the pre-pandemic period. Nomejko et al [15] argue that sexual dysfunction is not always related to lower sexual satisfaction.…”
Section: Discussionsupporting
confidence: 91%
“…To summarize, the study did not find a direct relationship between sexual satisfaction and pandemic-related restrictions assessed using the stringency index, which is in line with some previous studies, showing no change in sexual satisfaction during the pandemic [18,39,42]. Pennanen-Iire et al [45] argued that the pandemic indirectly affects sexual function.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The final two papers in this set examined sexual relationship health and adjustment during COVID-19. Gauvin et al ( 2022 ) concluded that people in relationships were relatively resilient to the COVID-19 pandemic, with only slight declines in sexual pleasure, frequency of orgasms with a partner, and frequency of solitary orgasms compared to retrospective recall of pre-pandemic levels. Finally, Griffin et al ( 2022 ) found that self-reported sexual activity and the number of sexual partners decreased during the first wave of the pandemic in a sample 1051 LGBTQ + adults in the USA, but sexual activity was impacted by living arrangement and partner status.…”
mentioning
confidence: 99%